The Real Risks of Artificial Intelligence: Incidents from the early days of AI research are instructive in the current AI environment. - Parnas, David Lorge (Communications of the ACM, 2017)
The article discusses risks associated with the use of artificial intelligence (AI) in computer programming. Topics include concerns regarding AI replacing people in various fields and specialized professions, the possibility of AI methods using heuristic programming to lead to untrustworthy or dangerous devices and systems, and the appeal of artificial neural networks despite their inability to perform tasks more efficiently than conventional programs.